Detection of Siderophores Production and Inorganic Phosphate Solubilization by Local Isolates of Fluorescent Pseudomonas - Khlood. A. A. Al-Khafaji; Saffa, A. Raheem; Amar. M. Jwaad; Mohamed A. A. Raheem (Journal of Madenat Alelem University College, 2015)
The aim of this study was to detect pyrovidene production and siderophore characterization from local isolates of fluorescent Pseudomonas which were isolated from rhizospheric region of sorghum. The isolates were tested for inorganic phosphate solubilization and biofilm formation. All isolates produced pyrovidene and other siderophores on King B broth comparing with pseudomonas broth, nutrient broth enriched with 10% egg white and succinate broth. Characterization of siderophores indicated the presence of hydroxymate siderophores from all isolates while only two isolates produced catechole siderophore. All isolates showed an ability of solubilized inorganic phosphate with release of 1795 ppm by 2nf isolate as comparing with minimum release 89 ppm by 6nf isolate. Biofilm could be detected on broth when bacterial biofilm adhering to the glass tube, black color formed at top of bacterial growth with Congo red stain on solid medium and on the bottom of liquid medium.